2011
DOI: 10.4028/www.scientific.net/amr.278.393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effective and Internal Cyclic Stress Components in the Inconel Superalloy Fatigued at Elevated Temperature

Abstract: Abstract. Cyclic multiple step test in strain control have been performed on cylindrical specimens of cast polycrystalline Inconel 738LC and 792-5A superalloys at 800 °C in laboratory atmosphere. Hysteresis loops were analyzed according to the statistical theory of hysteresis loop. The effective and internal stress components were evaluated. The effective stress of γ´ precipitate has significant influence on the stress-strain response both materials. The stress amplitude in IN 792-5A is higher than in IN 738LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…According to [13,14], the incremental CSSC did not differ from the CSSC obtained on several specimens for copper, low-carbon steels, or nickel-based superalloys. Petrenec [15] and Smid [14] investigated two types of Inconel (738LC and 792-5A) cyclically strained at 23 • C and 800 • C within the blocks of cycles with step-wise increasing strain amplitudes and, subsequently, the stress-strain response of the Inconel was analyzed. Parameters of CSSC determined by using the short-cut procedure are in good agreement with the parameters of the standard CSSC at both used temperatures.…”
Section: Introductionmentioning
confidence: 80%
“…According to [13,14], the incremental CSSC did not differ from the CSSC obtained on several specimens for copper, low-carbon steels, or nickel-based superalloys. Petrenec [15] and Smid [14] investigated two types of Inconel (738LC and 792-5A) cyclically strained at 23 • C and 800 • C within the blocks of cycles with step-wise increasing strain amplitudes and, subsequently, the stress-strain response of the Inconel was analyzed. Parameters of CSSC determined by using the short-cut procedure are in good agreement with the parameters of the standard CSSC at both used temperatures.…”
Section: Introductionmentioning
confidence: 80%
“…The investigated material is the polycrystalline nickel-based superalloy IN-738 LC, which has the composition shown in Table 1. This material is a precipitation strengthened nickel-based superalloy with around 59 vol.% of cuboid shaped γ' embedded in the γ matrix with grain sizes up to 3 mm in dependence of the manufacturing process and specimen design [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…This agrees well with previous works. [22][23][24] While the first peak (at lower fictive stresses, attributed to the matrix) gradually grows and shifts toward lower fictive stresses, the second peak (at higher stresses, attributed to the γ 0 precipitates) vanishes completely in less than 10 cycles. It shows that at room temperature the number of deformed microvolumes with high fictive stress substantially decreases and mobile dislocations can rapidly either avoid γ 0 precipitates or effectively shear them.…”
Section: Cyclic Deformation Behavior At Room Temperaturementioning
confidence: 99%
“…20,21 Pol ak et al 22 demonstrated its feasibility for fatigue analysis of multiphase materials, but only a few studies coupled the statistical approach with high-resolution microscopy inspection. 23,24 The structure of persistent slip bands and their interaction with precipitates was studied using high-resolution transmission electron microscopy. The surface relief and the location and mechanism of fatigue crack initiation are studied at room and elevated temperature of 800 C.…”
Section: Introductionmentioning
confidence: 99%